1995
DOI: 10.1002/pro.5560041104
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of residues in the homeodomain sequence family

Abstract: Homeodomains are 60 amino acid DNA binding domains found in numerous eukaryotic transcription factors. The homeodomain family is a useful system for studying sequence-structure relationships because several hundred sequences are known and the structures of several homeodomains have been determined. Covariation of amino acid residues in the homeodomain family has been investigated to see whether strongly covariant residue pairs can be understood in terms of the structure and function of these domains. Among 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
74
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 16 publications
0
74
0
Order By: Relevance
“…Thus, as a first step, the hydrophobic pair Val 19 /Ile 30 , present in the wild-type polypeptide, was replaced by salt bridges of different polarities, either isolated or networked. A previous statistical analysis of the information stored in the homeodomain resource data base (8,9) revealed an intriguing correlation between the nature of pair 19/30 and the loop residue 26 (proline or a branched aliphatic amino acid in all cases). Considering this, both salt bridges and aliphatic residues connecting 19/30 were also considered in the context of either proline or leucine in 26.…”
mentioning
confidence: 99%
“…Thus, as a first step, the hydrophobic pair Val 19 /Ile 30 , present in the wild-type polypeptide, was replaced by salt bridges of different polarities, either isolated or networked. A previous statistical analysis of the information stored in the homeodomain resource data base (8,9) revealed an intriguing correlation between the nature of pair 19/30 and the loop residue 26 (proline or a branched aliphatic amino acid in all cases). Considering this, both salt bridges and aliphatic residues connecting 19/30 were also considered in the context of either proline or leucine in 26.…”
mentioning
confidence: 99%
“…In a covariance analysis of 60 homeodomain protein sequences, Clarke (1995) has observed that residue pairs 19/30. 3 1/42, and 17/52 are among the most strongly correlated covariant residue pairs.…”
mentioning
confidence: 99%
“…3 1/42, and 17/52 are among the most strongly correlated covariant residue pairs. Moreover, the nature of these covariances generally functions to preserve salt bridges at these three surface sites (Clarke, 1995). The energetic basis of the requirement for these surface salt bridges is not yet certain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A single point mutation might ease or complicate each imaginable path of mutation at any other position in the complex, regardless of its distance from the interface (Lovell and Robertson 2010). In fact, co-evolution events have been detected affecting sites that are distant structurally (Gobel et al 1994;Clarke 1995;Gloor et al 2005;Fares and McNally 2006). On the other hand, the probability of correlated amino acid changes is closely related to the chemical nature of changes.…”
Section: Co-evolution Methodsmentioning
confidence: 99%